Temporal Changes in Nuclear Envelope Permeability during Semi-Closed Mitosis in Dictyostelium Amoebae - Kristina Mitic; Irene Meyer; Ralph Gräf; Marianne Grafe (Cells, 2023)
The Amoebozoan Dictyostelium discoideum exhibits a semi-closed mitosis in which the nuclear membranes remain intact but become permeabilized to allow tubulin and spindle assembly factors to access the nuclear interior. Previous work indicated that this is accomplished at least by partial disassembly of nuclear pore complexes (NPCs). Further contributions by the insertion process of the duplicating, formerly cytosolic, centrosome into the nuclear envelope and nuclear envelope fenestrations forming around the central spindle during karyokinesis were discussed. We studied the behavior of several Dictyostelium nuclear envelope, centrosomal, and nuclear pore complex (NPC) components tagged with fluorescence markers together with a nuclear permeabilization marker (NLS-TdTomato) by live-cell imaging. We could show that permeabilization of the nuclear envelope during mitosis occurs in synchrony with centrosome insertion into the nuclear envelope and partial disassembly of nuclear pore complexes. Furthermore, centrosome duplication takes place after its insertion into the nuclear envelope and after initiation of permeabilization. Restoration of nuclear envelope integrity usually occurs long after re-assembly of NPCs and cytokinesis has taken place and is accompanied by a concentration of endosomal sorting complex required for transport (ESCRT) components at both sites of nuclear envelope fenestration (centrosome and central spindle).